Islamization in Modern South Asia: Deobandi Reform and the Gujjar Response - Singh, David Emmanuel (Religion and society, 2012)
The religious identity of indegenous Gujjars in the Himilayan region remains largely unexplored. This book argues that their choice to associate with Deobandi Islam occurs in the wider context of conservation debates, local government-led efforts to relocate them from the Rajaji National Park in Uttarakhand, India, and the failure of NGOs to represent their interests. Based on documents and interviews, this detailed work explores both the continuing expansion of Deobandi reform and the responses of the Gujjars. It points toward the role of Islam in integrating marginal groups in South Asia. David Emmanuel Singh, Oxford Centre for Mission Studies, UK.